The Social Management in the Universidad Nacional Intercultural de la Amazonía and its Relationship with the Implementation of an Educational Policy with an Intercultural Approach - Castillo Farroñay, Zamia Ivon (2021)
The implementation process of any policy or program is complex in itself and can present a series of factors that hinder its development. The establishment of an educational policy with an intercultural approach is no stranger to this, since —like any process— it must be implemented and then evaluated. This article intends to reflect on these forms of implementation carried out in a specific context: the National Intercultural University of the Amazon (UNIA), since it is known that it develops the intercultural approach as part of its long-term vision. To this end, we refer to the achievements and limitations that this system entails and present a proposal of axes and indicators for this management system that contribute to the implementation process of the intercultural approach. In addition, we emphasize the need to reformulate methodological teaching-learning strategies that consider as part of their contents the knowledge developed by the different native peoples existing in our country and the functioning and promotion of the language by native and non-native students. Finally, the UNIA has important achievements in its social management system; however, it needs to take into consideration issues such as capacity building, articulation with allied institutions, rethinking teaching - learning strategies and a curricular proposal that takes into consideration the linguistic and cultural situation of its students (treatment of languages, promotion of scientific research, among others).